Correlation between ultrasonic and radiographic imaging of developmental dysplasia of the hip - Spaans, A. J. (J Child Orthop, 2019)
PURPOSE: The correlation between the degree of developmental hip dysplasia (DDH) measured on ultrasound images compared with that measured on radiographs is not clear. Most studies have compared ultrasonography (US) and radiographic images made at different times of follow-up. In this study the correlation between US images and radiographs of the hip made on the same day was evaluated. METHODS: US images and radiographs of both hips of 74 infants, who were treated for stable DDH, were reviewed in a retrospective study. Only infants who had an US examination and a radiograph on the same day were included. RESULTS: The correlation between α-angle of Graf and femoral head coverage on US was strong (p ≤ 0.0001). Weak correlations were found between the acetabular index of Tönnis on radiographs and α-angle of Graf on US (p = 0.049) and between acetabular index of Tönnis on radiographs and femoral head coverage of Morin on US (p = 0.100). CONCLUSION: This study reports on the correlation between US and radiographic imaging outcomes, both made on the same day in patients for treatment and follow-up of DDH. LEVEL OF EVIDENCE: IV